Prosecutor v. Jean-Pierre Bemba Gombo - Sadat, Leila Nadya (The American journal of international law, 2019)
On June 8, 2018, in a surprising turn, the Appeals Chamber of the International Criminal Court (ICC) reversed the conviction of Jean-Pierre Bemba Gombo and acquitted him of crimes against humanity and war crimes. The four separate opinions, raising questions about Pre-Trial and Trial Chamber procedures, the standard of Appellate Chamber review, and the scope of command responsibility, have revealed sharp disagreements between ICC judges and created considerable confusion over the state of ICC law and procedure.